2022
DOI: 10.1155/2022/7977335
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Application and Optimization Strategy of the LMBP Algorithm in Supply Chain Performance Evaluation

Abstract: In recent years, with the emergence of new technologies, big data, artificial intelligence, and other technologies have had a greater impact on supply chain management. Among them, big data analysis capability, as one of the important capabilities that supply chain enterprises should have, has a particularly significant impact on supply chain resilience management. From the perspective of performance management, based on supply chain resilience theory, the relationship between the supply chain performance mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The incorporation of big data in sustainable supply chain management has gained increasing popularity among researchers globally, with a focus on promoting overall coordinated development and increasing enterprise competitiveness (Zhang et al, 2020; Morales & Día-Serna, 2021). However, there is a need for further exploration of the impact of big data analysis capability on supply chain performance, particularly in relation to supply chain collaboration and resilience (Babarinde et al, 2023;Gu, 2022).…”
Section: Case Studies Of Reviewing the Use Of Big Data In Supply Chai...mentioning
confidence: 99%

Reviewing the use of big data in supply chain optimization in the USA

Israel Osejie Okoduwa,
Bankole Ibrahim Ashiwaju,
Jeremiah Olawumi Arowoogun
et al. 2024
World J. Adv. Res. Rev.
“…The incorporation of big data in sustainable supply chain management has gained increasing popularity among researchers globally, with a focus on promoting overall coordinated development and increasing enterprise competitiveness (Zhang et al, 2020; Morales & Día-Serna, 2021). However, there is a need for further exploration of the impact of big data analysis capability on supply chain performance, particularly in relation to supply chain collaboration and resilience (Babarinde et al, 2023;Gu, 2022).…”
Section: Case Studies Of Reviewing the Use Of Big Data In Supply Chai...mentioning
confidence: 99%

Reviewing the use of big data in supply chain optimization in the USA

Israel Osejie Okoduwa,
Bankole Ibrahim Ashiwaju,
Jeremiah Olawumi Arowoogun
et al. 2024
World J. Adv. Res. Rev.
“…The degree of information sharing is the degree to which companies in the supply chain trust each other and share information [ 41 ]. Synergistic partners reflect not only the number of collaborators in the supply chain, but also the time and cost required to change the time it takes to change collaborators [ 42 ]. In addition, enterprises in the supply chain can also enhance supply chain collaboration through effective communication, trust and information sharing, thereby enhancing the speed of response to supply chain risks and ultimately improving supply chain resilience.…”
Section: Supply Chain Resilience Evaluation Index Systemmentioning
confidence: 99%
“…Some scholars have found that urbanization aggravates environmental pollution. Conversely, urbanization can exert a notable mitigating influence on environmental pollution [17]. Some studies aim to verify whether the classical EKC curve exists.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies aim to verify whether the classical EKC curve exists. Consequently, many scholars take different countries and regions as examples to empirically analyze this problem, such as [17,18]. In particular, Martinez and Maruotti demonstrated the existence of an inverted U-shaped link between urbanization and CO 2 emissions in developing countries.…”
Section: Introductionmentioning
confidence: 99%